2017
DOI: 10.1111/mve.12225
|View full text |Cite
|
Sign up to set email alerts
|

First report of Stegomyia aegypti (= Aedes aegypti) in Mexico City, Mexico

Abstract: Stegomyia aegypti (= Aedes aegypti) (Diptera: Culicidae) is a species of mosquito that is currently widespread in Mexico. Historically, the mosquito has been distributed across most tropical and subtropical areas lower than 1700 m a.s.l. Currently, populations that are found at higher altitudes in regions with cold and dry climates suggest that these conditions do not limit the colonization and population growth of S. aegypti. During a survey of mosquitoes in September 2015, larvae of S. aegypti mosquitoes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Both sites are places that experience massive local and non-local human transit. We presume that an accidental introduction of eggs, larvae, pupae, and/or adults into the region occurred by human transit [4]. However, the 2016–2017 collections were recorded at public parks, museums, residential areas and cemeteries, indicating the possible presence of transitory colonies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both sites are places that experience massive local and non-local human transit. We presume that an accidental introduction of eggs, larvae, pupae, and/or adults into the region occurred by human transit [4]. However, the 2016–2017 collections were recorded at public parks, museums, residential areas and cemeteries, indicating the possible presence of transitory colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Is a destination and point of departure of most international flights, including those which use the city as a stopover from Central and South America, the US and Europe. It is the most urbanized and populous city of the country (8,985,339 people) with a relative small area (1485.5 km 2 ) [4]. The city is located at the Basin of Mexico (Fig 1), in an elevated valley at an altitude of about 2,240 m [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti and Ae. albopictus are the primary mosquito species known for transmitting arboviruses (Flores-Suarez et al, 2016; Dzul-Manzanilla et al, 2016; Huerta et al, 2017) and have generally been reported ubiquitous (Ortega-Morales and Rodriguez, 2016; Kuri-Morales et al, 2017). They are both linked with the transmission of several arboviruses such as dengue, Zika, Chikungunya, and Yellow fever (von Seidlein et al, 2017; Benedict et al, 2007; Serpa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported Ae. aegypti present in 28 states of Mexico (Ibáñez-Bernal & Martínez-Campos 1994a;Mora-Covarrubias et al 2010;Ávila-Rodríguez et al 2012;Espinoza-Gómez et al 2013;Kuri-Morales et al 2017). In addition, Ae.…”
Section: Introductionmentioning
confidence: 99%